The Interplay of Traits, Phylogeny and Abundance Shapes Spatial Mammal Diversity Patterns - Kay Zin Than; Alice C. Hughes; Lin Wang; Zaw Zaw; Rui‐Chang Quan (Global Ecology and Biogeography, 2025)
Aim Terrestrial mammal communities are crucial indicators of tropical ecosystem health and sustainability. However, the role of shared species responses driven by functional traits and phylogenetic relatedness in shaping community assembly remains underexplored for identifying conservation hotspots. Spatial predictions of species diversity also remain limited by approaches that fail to jointly account for species occupancy and abundance. This study evaluates trait‐ and phylogeny‐informed environmental filtering in structuring mammal communities and maps spatial diversity patterns by integrating species occupancy and abundance across spatial–temporal scales. Ultimately, areas of high mammal diversity reflecting underlying assembly processes are identified to guide regional conservation planning. Location Myanmar and China. Time Period 2015–2021. Major Taxa Studied Terrestrial mammals. Methods We deployed 936 camera traps over 6 years across Upper Myanmar and Xishuangbanna, China, using a nested sampling design that ensured robust spatial–temporal replication, and analysed the data using community hierarchical models. Results Climate and habitat factors predominantly drive species richness, while traits and phylogenetic relatedness jointly shape distinct community patterns. Seasonal variation in local diversity underscores the role of environmental filtering in structuring mammal communities across space and time. Large‐bodied omnivores favour stable temperature niches, whereas reduced precipitation filters communities towards wide‐ranging mammals. Anthropogenic disturbances and forest cover loss alter community structure, diminishing the prevalence of carnivorous traits. Predictive community maps with uncertainty estimates guide future survey efforts through a more integrative, data‐informed approach to regional planning. Main Conclusions This study presents a novel framework for improving climate‐ and habitat‐based biodiversity models by integrating trait‐ and phylogeny‐informed assembly processes with abundance‐based predictions across suitable habitats. The findings, including phylogenetically clustered niches in Cervidae and Felidae, suggest that shared evolutionary adaptations, such as temperature tolerance in ungulates and disturbance tolerance in carnivores, shape community assembly under varying environmental pressures and can inform spatial conservation prioritisation.

Conservation planning on China's borders with Myanmar, Laos, and Vietnam - Lin Wang; Bin Yang; Yang Bai; Xiaoqiang Lu; Richard T. Corlett; Yunhong Tan; Xiao‐Yong Chen; Jianguo Zhu; Yan Liu; Rui‐Chang Quan (Conservation Biology, 2021)
Transboundary conservation is playing an increasingly important role in maintaining ecosystem integrity and halting biodiversity loss caused by anthropogenic activities. However, lack of information on species distributions in transboundary regions and understanding of the threats in these areas impairs conservation. We developed a spatial conservation plan for the transboundary areas between Yunnan province, southwestern China, and neighboring Myanmar, Laos, and Vietnam in the Indo‐Burma biodiversity hotspot. To identify priority areas for conservation and restoration, we determined species distribution patterns and recent land‐use changes and examined the spatiotemporal dynamics of the connected natural forest, which supports most species. We assessed connectivity with equivalent connected area (ECA), which is the amount of reachable habitat for a species. An ECA incorporates the presence of habitat in a patch and the amount of habitat in other patches within dispersal distance. We analyzed 197,845 locality records from specimen collections and monographs for 21,004 plant and vertebrate species. The region of Yunnan immediately adjacent to the international borders had the highest species richness, with 61% of recorded species and 56% of threatened vertebrates, which suggests high conservation value. Satellite imagery showed the area of natural forest in the border zone declined by 5.2% (13,255 km 2 ) from 1995 to 2018 and monoculture plantations increased 92.4%, shrubland 10.1%, and other cropland 6.2%. The resulting decline in connected natural forest reduced the amount of habitat, especially for forest specialists with limited dispersal abilities. The most severe decline in connectivity was along the Sino‐Vietnamese border. Many priority areas straddle international boundaries, indicating demand and potential for establishing transboundary protected areas. Our results illustrate the importance of bi‐ and multilateral cooperation to protect biodiversity in this region and provide guidance for future conservation planning and practice.

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.